The holy mass - Aquilina, Mike; Weinandy, Thomas G. (Thomas Gerard) (Sayings of the fathers of the church., 2021)
"Sayings of the early Church fathers on all aspects of the Catholic Mass, drawn largely from the Catholic University of America's Fathers of the Church series"--